AMPK Promotes Xenophagy Through ‘Priming’ of Autophagic Kinases upon Detection of Salmonella Outer Membrane Vesicles - To, Truc (Université d'Ottawa / University of Ottawa, 2019)
The autophagy pathway is an essential component of the innate immune response, capable of rapidly targeting intracellular bacteria, which are subsequently degraded by lysosomal enzymes. Recent work has begun to elucidate the regulatory signalling for autophagy induction in response to pathogenic bacteria. However, the initial signalling regulating autophagy induction in response to the detection of pathogens remains largely unclear. Here we report that AMPK, an important upstream activator of the autophagy pathway, is rapidly stimulated upon detection of pathogenic bacteria, prior to bacterial invasion. Bacterial recognition is initially achieved through detection of outer membrane vesicles (OMVs). Additionally, we show that AMPK signalling relieves mTORC1-mediated repression of the autophagy pathway in response to Salmonella infection, positioning the cell for a rapid induction of autophagy. Surprisingly, we found that the activation of AMPK and inhibition of mTORC1 in response to extracellular Salmonella are not accompanied by an induction of bulk autophagy. However, upon Salmonella invasion AMPK signalling is required for efficient and selective targeting of bacteria-containing vesicles by the autophagy pathway through activation of pro-autophagic kinase complexes. Collectively, these results demonstrate a key role for AMPK signalling in coordinating the rapid autophagic response prior to invasion of pathogenic bacteria.
Keywords: Autophagy; Cellular signalling; Xenophagy; Infection; Salmonella